#### Answer

$\frac{t-3}{3}$

#### Work Step by Step

$\frac{t^{2}-9}{3t+9}=\frac{(t+3)(t-3)}{3(t+3)}=\frac{t-3}{3}\times\frac{t+3}{t+3}=\frac{t-3}{3}\times1=\frac{t-3}{3}$

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$\frac{t-3}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.